الموضوعات الصوفية في قصة حي بن يقضان -دراسة موضوعاتية فنية - لورو, لورو, علي حياة (University of El-oued, 2022)
في هذا البحث، عمل أدبي مهم، تمثل في قصة "حي بن يقظان" للأديب والمفكر الأندلسي "ابن الطفيل". حيث قمنا بدراسة أهم الموضوعات الصوفية المستخلصة من هذه القصة، كرحلة البحث عن الله والمعرفة الذوقية وبعض الأحوال والمقامات المتعلقة بالتربية الروحية. كما أشرنا إلى أبرز الجوانب الفنية المشكلة لجمالية هذه العمل، من دراسة للغة وعناصر القصة وبعض الصور الفنية التي صنعت تميز هذا النتاج الأدبي. In this research, we dealt with an important literary work, represented in the story "Hayy Bin Yaqzan" by the Andalusian writer and thinker "Ibn Al-Tufail". Where we have studied the most important mystical topics extracted from this story, such as the journey of searching for God, taste knowledge, and some appreciating knowledge Conditions and Standings related to spiritual education. We also referred to the most prominent technical aspects that formed the aesthetics of this work, from a study of the language, elements of the story and some artistic images that were made to distinguish this literary production.
Keywords: الصوفية –القصة –الصور الفنية; story - artistic images